1976
DOI: 10.3109/07435807609073910
|View full text |Cite
|
Sign up to set email alerts
|

Post-Coital Contraceptive Effects of an Agonistic Analogue of Luteinizing Hormone Releasing Hormone

Abstract: An analogue of synthetic hypothalamic LRH, D-[ALA]6-DES-[GLY]10-PRO9-ethylamide-LRH (Wy-18,481) was evaluated for agonistic (in vivo LH-releasing and ovulation-inducing), post-coital contraceptive and reproductive target organ effects. Both LRH and the analogue terminated pregnancy; there appeared to be a direct relationship between agonistic and post-coital contraceptive potency and activity. The analogue proved to be a potent agonist and both a pre-and post-implantational post-coital anti-fertility agent. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Other studies revealed that if such agonist-treated animals with identifiable resorption sites are permitted to term (day [22][23][24], total resorption will have occurred (15). The collective data herein reported, reinforced by studies employing other agonists (14), clearly attest to the antipregnancy properties of this peptide class, fortify the agonist/postcoital contraceptive relationship, and stress that the greater the agonist property, the greater the antifertility property.…”
Section: Anti-fertility Properties Of Lh-rh and Agonistssupporting
confidence: 58%
See 3 more Smart Citations
“…Other studies revealed that if such agonist-treated animals with identifiable resorption sites are permitted to term (day [22][23][24], total resorption will have occurred (15). The collective data herein reported, reinforced by studies employing other agonists (14), clearly attest to the antipregnancy properties of this peptide class, fortify the agonist/postcoital contraceptive relationship, and stress that the greater the agonist property, the greater the antifertility property.…”
Section: Anti-fertility Properties Of Lh-rh and Agonistssupporting
confidence: 58%
“…There was much aspiration for its potential value in correcting gynec o p a t h y and andropathic states, thus stimulating an ambitious endeavor to synthesize more potent and longer acting congeners (26,27). In spite of the considerable success achieved in generating these highly potent LH-releasing analogues, additional testing undoubtedly confirmed the antireproductive nature of this class of compounds, and further corroborated the direct relationship to their agonist properties (14,15). T h e various hormonal and receptor studies begin to explain the mechanisms by which the excessive and inappropriate hypophysial stimulation fraught by the "super" analogues is injurious to the reproductive integrity of the animal, be it female or male, immature or mature, and why, in a considerable number of clinical studies, the analogues are truly incapable of significantly ameliorating or reversing the infertile or hypogonadal state (15).…”
Section: Commentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, multiple high doses of leuprolide were found to effect regression of hormone-dependent mammary tumors (3,4) and to have birth control potential in both sexes (5)(6)(7)(8).…”
mentioning
confidence: 99%